Does nutrition-sensitive social protection build longer-term resilience? Experimental evidence from Bangladesh - Ahmed, Akhter; Bakhtiar, M. Mehrab; Hoddinott, John F.; Roy, Shalini (International Food Policy Research Institute, 2024)
Evidence shows that cash and in-kind transfer programs increase food security while interventions are ongoing, including during or immediately after shocks. But less is known about whether receipt of these programs can have protective effects for household food security against shocks that occur several years after interventions end. We study the effects of a transfer program implemented as a cluster-randomized control trial in rural Bangladesh from 2012-2014 – the Transfer Modality Research Initiative (TMRI) – on food security in the context of the COVID-19 pandemic. We assess TMRI’s impacts at three post-program time points: before the shock (2018), amidst the shock (2021), and after the immediate effects of the shock (2022). We find that TMRI showed protective effects on household food security during and after the pandemic, but program design features “mattered”; positive impacts were only seen in the treatment arm that combined cash transfers with nutrition behavior change communication (Cash+BCC). Other treatment arms – cash only, and food only – showed no significant sustained effects on our household food security measures after the intervention ended, nor did they show protective effects during the pandemic. A plausible mechanism is that investments made by Cash+BCC households in productive assets – specifically livestock – increased their pre-shock resilience capacity.